2002
DOI: 10.1128/iai.70.3.1260-1271.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Ganglioside GM1-Binding Ability, Pentamer Formation, and Epitopes of Cholera Toxin B (CTB) Subunits and CTB/Heat-Labile Enterotoxin B Subunit Chimeras

Abstract: Variants of cholera toxin B subunit (CTB) were made by bisulfite-and oligonucleotide-directed mutagenesis of the ctxB gene. Variants were screened by a radial passive immune hemolysis assay (RPIHA) for loss of binding to sheep erythrocytes (SRBC). Variant CTBs were characterized for the formation of immunoreactive pentamers, the ability to bind ganglioside GM 1 in vitro, and reactivity with a panel of monoclonal anti-CTB antibodies. Substitutions at eight positions (i.e., positions 22, 29, 36, 45, 64, 86, 93, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…pARCT5 is an arabinose-inducible clone derived from pAR3 (21) expressing an operon containing the ctxA and ctxB genes with signal sequences derived from the LTIIb B gene and using the T7g10 Shine-Dalgarno sequence (15,16). pARCT5 is a derivative of pARCT4 containing a unique, translationally silent PstI site within ctxA1 (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…pARCT5 is an arabinose-inducible clone derived from pAR3 (21) expressing an operon containing the ctxA and ctxB genes with signal sequences derived from the LTIIb B gene and using the T7g10 Shine-Dalgarno sequence (15,16). pARCT5 is a derivative of pARCT4 containing a unique, translationally silent PstI site within ctxA1 (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…6). In wild-type mononuclear preosteoclasts and multinucleated osteoclasts, Atp6v0d2 staining was more intense on the plasma membrane than in the perinuclear region, and a large amount of Atp6v0d2 was colocalized with the plasma membrane marker GM-1 ganglioside, which is a receptor of cholera toxin subunit B (56). In contrast, in LDLR Ϫ/Ϫ preosteoclasts, Atp6v0d2 remained abundant in the cytoplasm and in the perinuclear region, and little colocalization with GM-1 ganglioside was observed (Fig.…”
Section: Figure 3 Osteoclast Differentiation Signaling and Expressiomentioning
confidence: 96%
“…CTx binding was the first described GSL receptor function (Heyningen 1974). The B subunit-GM1 oligosaccharide has been cocrystallized to resolve the binding site (Merritt et al 1994), but within this site, only tyrosine 12 was found crucial for GM1 binding (Jobling and Holmes 2002). B subunit-GM1 binding mediates the internalization of the holotoxin and its subsequent retrograde transport through endosomes, trans-Golgi network, and Golgi to the endoplasmic reticulum, in which the A subunit separates and is transported through the Sec61 translocon into the cytosol (Schmitz et al 2000).…”
Section: Membrane Gsl Receptors For Exogenous Microbial Virulence Facmentioning
confidence: 99%